The effects of COVID-19 lockdown measures on health and healthcare services in Uganda. - David Musoke; Sarah Nalinya; Grace Biyinzika Lubega; Kevin Deane; Elizabeth Ekirapa-Kiracho; David McCoy (Public Library of Science (PLoS), 2023)
Many countries across the world instituted lockdowns as a measure to prevent the spread of COVID-19. However, these lockdowns had consequences on health systems. This study explored effects of the COVID-19 lockdown measures on health and healthcare services in Uganda. The qualitative study employed focus group discussions (FGDs), household interviews, and key informant interviews (KIIs) in both an urban (Kampala district) and rural (Wakiso district) setting in central Uganda. Fourteen FGDs were conducted among community members, local leaders, community health workers, and health practitioners. Interviews were conducted among 40 households, while 31 KIIs were held among various stakeholders including policy makers, non-governmental organisations, and the private sector. Data was analysed by thematic analysis with the support of NVivo 2020 (QSR International). Findings from the study are presented under four themes: maternal and reproductive health; child health; chronic disease services; and mental health. Maternal and reproductive health services were negatively affected by the lockdown measures which resulted in reduced utilisation of antenatal, postnatal and family planning services. These effects were mainly due to travel restrictions including curfew, and fear of contracting COVID-19. The effects on child health included reduced utilisation of services which was a result of difficulties faced in accessing health facilities because of the travel restrictions. Patients with chronic conditions could not access health facilities for their routine visits particularly due to suspension of public transport. Depression, stress and anxiety were common due to social isolation from relatives and friends, loss of jobs, and fear of law enforcement personnel. There was also increased anxiety among health workers due to fear of contracting COVID-19. The COVID-19 lockdown measures negatively affected health, and reduced access to maternal, reproductive and child health services. Future interventions in pandemic response should ensure that their effects on health and access to health services are minimised.